Criminological-epistemological and gender aspects of the crime of rape (Archives of Criminology, 2010)
According to government information from November 2010, only 8% of committed sex crimes are reported in Poland. In 90% of cases, the perpetrators remain unpunished. Taking into account the statistics for 2009, 6,700 cases of sexual violence show the scale of the problem. The article tries to investigate the reasons of such situation. How does it happen that in a legal order, which since 1932 is based on extremely modern approach to the crime of rape, it remains in practice so often unpunished? The reasons of this are seen in the accepted procedure of prosecution, on the motion of the injured. This procedure results from the fact that provisions from 1932 have been accepted as they were, without a deeper reflection or analysis of the state of affairs of the time. What was acceptable in the criminological-epistemological and dogmatic perspective then, has been accepted by the legislator at present. This leaves a question why regulations from 1932 are still in force at present, with the detriment to the victims. In seeking an answer to this question, a methodology provided by feminist jurisprudence is assumed. The text also explains the very notion of feminist jurisprudence and gender analysis of law. The method allows to notice the elements earlier neglected by the law and to explain why corruption of the perpetrator reaches the victim. The development of feminist jurisprudence over the past three decades has contributed to significant enrichment of the theory of law in many countries and has led to many reforms of criminal law, including changes to the regulations concerning the rape of crime. Taking feminist criminology and feminist jurisprudence into account allows to consider the causes of placing joint responsibility for rape on a victim. It allows to demonstrate that what is hidden under the euphemism of morals and morality is also supported by laws and does not result from tradition as much as from the influence of contemporary law. The accepted procedure of prosecution of the crime is a significant element of this process. Assuming a gender perspective introduces a perspective of experiences and values essential for women to the analysis of language, evaluation and events, although it is not limited to this. The text, while analysing the determinants of regulations concerning rape, questions the basic axioms of criminal law dogma pertaining to neutrality and objectivity of criminal law. The example of regulations on rape proves that both axioms in fact sustain a loss to the benefit of the interest of the legislator who has a greater tendency to identify with a perpetrator than with a victim. The text analyses various perspectives of justifying accepted norms and indicates that higher arguments at each time serve to justify current interests. Using instruments of gender analysis of law here as well, reader’s attention is drawn to the perspective resulting from the experiences and values presented by women.